2017
DOI: 10.3847/1538-4357/aa93f7
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Large-scale Quasi-circular Secondary Ribbon Associated with Successive Flares and a Halo CME

Abstract: Solar flare ribbons provide an important clue to the magnetic reconnection process and associated magnetic field topology in the solar corona. We detected a large-scale secondary flare ribbon of a circular shape that developed in association with two successive M-class flares and one CME. The ribbon revealed interesting properties such as 1) a quasi-circular shape and enclosing the central active region; 2) the size as large as 500 by 650 , 3) successive brightenings in the clockwise direction at a speed of 16… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Slipping motion of flare ribbons were not only observed in circular flare ribbons (e.g., Masson et al 2009;Liu et al 2013;Jiang et al 2015;Romano et al 2017;Lim et al 2017;Li et al 2018), but also in many other kinds of flare ribbons (e.g., Dudík et al 2014Dudík et al , 2016Li et al 2016;Zheng et al 2016;Lörinčík et al 2019). The slipping speeds reported in previous studies are ranged from 30 to 450 km s −1 .…”
Section: Conclusion and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Slipping motion of flare ribbons were not only observed in circular flare ribbons (e.g., Masson et al 2009;Liu et al 2013;Jiang et al 2015;Romano et al 2017;Lim et al 2017;Li et al 2018), but also in many other kinds of flare ribbons (e.g., Dudík et al 2014Dudík et al , 2016Li et al 2016;Zheng et al 2016;Lörinčík et al 2019). The slipping speeds reported in previous studies are ranged from 30 to 450 km s −1 .…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…So far, only one study reported the round-trip slipping motion along the inner flare ribbon (Wang & Liu 2012). The slipping motion of circular flare ribbons towards a certain direction have been observed in a few cases (e.g., Masson et al 2009;Liu et al 2013;Jiang et al 2015;Romano et al 2017;Lim et al 2017;Li et al 2018), but round-trip slipping motion of circular flare ribbon has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fan-spine morphology has been extensively investigated, the previous studies are mainly dedicated to the formation and changes of magnetic configuration and the associated explosive events (e.g., Guglielmino et al 2010;Jiang et al 2015;Yang et al 2015c;Lim et al 2017;Kumar et al 2019), and there is no simultaneous imaging and spectral study on the null point during solar flare. In this paper, we study a fan-spine structure in active region (AR) 12736 on 2019 March 22, and focus on the null point where magnetic reconnection occurred during a B6.7 flare, combing the high-quality vector magnetograms from the Hinode (Kosugi et al 2007) with the high-resolution imaging and spectral observations from the New Vacuum Solar Telescope (NVST; Liu et al 2014), the Solar Dynamics Observatory (SDO; Pesnell et al 2012), and the Interface Region Imaging Spectrograph (IRIS ; De Pontieu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a circular ribbon flare, null-point reconnection occurs and accelerates particles, which subsequently flow along the separatrix surface and the spine field into the lower atmosphere. As a result, the circular ribbon is formed at the intersection of the dome-shaped fan and the lower atmosphere (Hao et al 2017;Masson et al 2017;Xu et al 2017;Lim et al 2017). When the outer spine field is connected to a remote field, a remote brightening ribbon would appear (Reid et al 2012;Li et al 2017a;Hernandez-Perez et al 2017).…”
Section: Introductionmentioning
confidence: 99%